2016
DOI: 10.1073/pnas.1611424113
|View full text |Cite
|
Sign up to set email alerts
|

SCAP/SREBP pathway is required for the full steroidogenic response to cyclic AMP

Abstract: Luteinizing hormone (LH) stimulates steroidogenesis largely through a surge in cyclic AMP (cAMP). Steroidogenic rates are also critically dependent on the availability of cholesterol at mitochondrial sites of synthesis. This cholesterol is provided by cellular uptake of lipoproteins, mobilization of intracellular lipid, and de novo synthesis. Whether and how these pathways are coordinated by cAMP are poorly understood. Recent phosphoproteomic analyses of cAMP-dependent phosphorylation sites in MA10 Leydig cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…We observed an interaction between GDF15 and SCAP (Fig.3A-3B). TGFβ1 has been reported to activate SREBF2 in kidney mesangial cells, and SREBF2 activation was dependent on SCAP [29,30]. In this study, knockdown of GDF15 decreased expression of SCAP, SREBF2, and HMGCR in siRNA-GDF15 ESCCs (Fig.3C), while SCAP overexpression could increase SREBF2 and HMGCR expression levels (Fig.4A) and reverse the migration, invasion, and EMT of GDF15-siRNA ESCCs (Fig.4B-4D).…”
Section: Discussionmentioning
confidence: 50%
“…We observed an interaction between GDF15 and SCAP (Fig.3A-3B). TGFβ1 has been reported to activate SREBF2 in kidney mesangial cells, and SREBF2 activation was dependent on SCAP [29,30]. In this study, knockdown of GDF15 decreased expression of SCAP, SREBF2, and HMGCR in siRNA-GDF15 ESCCs (Fig.3C), while SCAP overexpression could increase SREBF2 and HMGCR expression levels (Fig.4A) and reverse the migration, invasion, and EMT of GDF15-siRNA ESCCs (Fig.4B-4D).…”
Section: Discussionmentioning
confidence: 50%
“…However, the role of GDF15 in the invasion and metastasis of EC remains poorly understood. Both TGFβ1 and GDF15 belongs to TGF-β superfamily, TGFβ1 was reported to activate SREBP2 in kidney mesangial cells, SREBF2 activation was dependent on SCAP ( 11 , 12 ), SCAP or SREBPs promoted tumor progression in various cancer ( 13 ). Therefore, we speculated that GDF15 may also regulate the invasion and metastasis of EC through SCAP/SREBF2 axis, which involved cholesterol synthesis and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…TGFβ1 has been reported to activate the sterol regulatory element-binding protein 2 (SREBP2) in kidney mesangial cells, and SREBF2 activation was dependent on sterol regulatory element-binding protein cleavage-activating protein (SCAP) ( 11 , 12 ), inhibition of SCAP or SREBPs significantly suppressed tumor growth in various cancer ( 13 ). As a divergent member of the TGF-β superfamily, GDF15 may also promote the progression of EC through SCAP/SREBPs pathway.…”
Section: Introductionmentioning
confidence: 99%
“…10,16,32 Targeting SREBPs pathway critical for cholesterol biosynthesis provides an promising strategy to improve therapeutic option of lipid metabolic diseases. 1,14,15 In this study, we established a stable HepG2 cell line transfected with a vector containing the human pGL3-promoter coupled to rey luciferase reporter gene. The activity of luciferase varies with the expression levels of SREBPs in the transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Masami Shimizu-Albergine et al demonstrated that SCAP/SREBP pathway was required for maximal steroid hormone biosynthesis. 14 Tang et al suggested that botulin could be a promising lead compound for treatment of hyperlipidemia by inhibition SREBP pathway. 15 Inhibition of SREBP pathway could be employed as an alternative strategy to treat metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%